2020
DOI: 10.3390/ijerph17165806
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Correlated Internet and Smartphone Addiction in Adolescents: Copula Regression Analysis

Abstract: Internet and smartphone addiction have become important social issues. Various studies have demonstrated their association with clinical and psychological factors, including depression, anxiety, aggression, anger expression, and behavioral inhibition, and behavioral activation systems. However, these two addictions are also highly correlated with each other, so the consideration of the relationship between internet and smartphone addiction can enhance the analysis. In this study, we considered the copula regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 46 publications
2
11
0
Order By: Relevance
“…Tateno et al (2019) revealed a highly significant correlation of r = 0.67 ( p < 0.0001) between Internet addiction measured by the Internet Addiction Test (IAT) and smartphone addiction as measured by the Smartphone Addiction Scale–Short Version (SAS-SV) in a Japanese sample. In their study, Lee et al (2020) found a significant correlation of r = 0.49 ( p < 0.001) between Young’s Internet Addiction Test (Y-IAT) and the Smartphone Addiction Scale (SAS).…”
Section: Introductionmentioning
confidence: 98%
“…Tateno et al (2019) revealed a highly significant correlation of r = 0.67 ( p < 0.0001) between Internet addiction measured by the Internet Addiction Test (IAT) and smartphone addiction as measured by the Smartphone Addiction Scale–Short Version (SAS-SV) in a Japanese sample. In their study, Lee et al (2020) found a significant correlation of r = 0.49 ( p < 0.001) between Young’s Internet Addiction Test (Y-IAT) and the Smartphone Addiction Scale (SAS).…”
Section: Introductionmentioning
confidence: 98%
“…PSU shares some commonalities with the better-researched concept of internet use disorder (IUD) [ 16 , 17 , 18 , 19 ]. PSU usually involves: (i) spending a lot of time using the smartphone; (ii) unsuccessful attempts to reduce such behavior; (iii) reporting a positive mood when using it, while the mood changes to negative during offline periods; and (iv) reporting interpersonal problems (with family or friends, at work or school) due to excessive use [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it has been reported in a prospective study that there are bidirectional interactions between addiction and BIS/BAS (31). Importantly for this study, although few related studies have been conducted, some studies have revealed that BIS/BAS is closely related to PSU and can be risk factors for PSU (25,(32)(33)(34). For example, a study has found that BIS is significantly associated with PSU through copula regression analysis (33).…”
Section: Introductionmentioning
confidence: 89%
“…Importantly for this study, although few related studies have been conducted, some studies have revealed that BIS/BAS is closely related to PSU and can be risk factors for PSU ( 25 , 32 34 ). For example, a study has found that BIS is significantly associated with PSU through copula regression analysis ( 33 ). Overall, existing researches establish the close relationships between BIS/BAS and PSU.…”
Section: Introductionmentioning
confidence: 99%